Cold War Pavlov: Homosexual aversion therapy in the 1960s. (February 2021) - Davison, Kate
Homosexual aversion therapy enjoyed two brief but intense periods of clinical experimentation: between 1950 and 1962 in Czechoslovakia, and between 1962 and 1975 in the British Commonwealth. The specific context of its emergence was the geopolitical polarization of the Cold War and a parallel polarization within psychological medicine between Pavlovian and Freudian paradigms. In 1949, the Pavlovian paradigm became the guiding doctrine in the Communist bloc, characterized by a psychophysiological or materialist understanding of mental illness. It was taken up by therapists in Western countries who were critical of psychoanalysis and sought more 'scientific' diagnostic and therapeutic methods that focused on empirical evidence and treating actual symptoms. However, their attitude towards homosexuality often played a decisive role in how they used aversion therapy. Whereas Czechoslovakian researchers cautioned readers about low success rates and agitated for homosexual law reform in 1961, most of their anglophone counterparts selectively ignored or misrepresented the results of 'the Prague experiment', instead celebrating single-case 'success' stories in their effort to correct 'abnormal' sexual orientation. In histories of queer sexuality and its pathologization, the behaviourist paradigm remains almost entirely unmapped. This article provides the most detailed study to date of aversion therapy literature from both sides of the East/West border. In doing so, it contributes to the project not only of 'decentring Western sexualities', but of decentring Western sexological knowledge. Given its Pavlovian origins, the history of homosexual aversion therapy can be fully understood only in the context of Cold War transnational sexological knowledge exchange.